Plastic zone distribution and main controlling factors analysis of large mining height face in steeply dipping coal seam - Hao ZHANG; Yongping WU; Panshi XIE (Meitan kexue jishu, 2023)
Coal wall of large mining height face in steeply dipping coal seam has large free height, wide free movement space and poor self-stabilization balance, coal wall is not an isolated body in the face, it can form a load-bearing structure with the surrounding rock, supports and other mediators, and the mining behavior is closely linked. The dip angle effect can easily promote the dissimilation of the coal wall bearing environment, complicate its response behavior, increase the difficulty of coal wall and surrounding rock stability control, and restrict the safe and efficient production of the face. In order to solve the problem of coal wall stability control of large mining height face in steeply dipping coal seam, theoretical analysis and numerical calculation are comprehensively used for research. The stress in the plastic zone of large mining height face in steeply dipping coal seam increases exponentially, there is an asymmetric arch residual stress influence zone in the vicinity of the coal wall, the plastic zone breadth is dissimilated in different regions, and the width from large to small is the upper, middle and lower part, and the distribution pattern is in the shape of stepped arch, coal in the plastic zone bears repeated pressure, and will be enhanced with the expansion of plastic zone. As the mining height increases, the residual abutment pressure near the coal wall decreases, the compressive strength, displacement value and disturbed range of the coal in front of the coal wall will increase. The stress and transport of the coal wall under the dip angle effect develop in a zonal manner, in which the stress distribution is lower> upper> middle, while for the displacement is middle> upper> lower. In addition, the working face inclination under the oblique angle will lead to the transformation of the coal wall instability mode, when the oblique angle is large, the dip angle of face is small, the compression component of abutment pressure is enhanced, and the external convex spalling mainly occurs. On the contrary, it’s the sliding instability under the coupling of mining stress and self weight. The comprehensive analysis shows that the coal wall mining behavior is regionally heterogeneous under the coupling effect of dip angle and mining height, and because the stress unloading and migration in the middle and upper part of the face are larger, therefore the two regions should be the key prevention and control areas for coal wall instability of large mining height face in steeply dipping panel.